Online communities and social computing : 5th International conference, OCSC 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013. Proceedings - Zaphiris, Panayiotis; Ozok, A. Ant (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Online Communities and Social Computing, OCSC 2013, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 49 contributions was carefully reviewed and selected for inclusion in the OCSC proceedings. The papers are organized in the following topical sections: user behavior and experience in online social communities; learning and gaming communities; society, business and health; designing and developing novel online social experiences.